Risk factors of preeclampsia - Honesty Pujiyani; Melyana Nurul Widyawati; Asiswari Asiswari (Jurnal Kesehatan Ibu dan Anak, 2018)
Preeclampsia affects about 4% of all pregnancies and is the major cause of maternal morbidity and mortality, fetal, and neonatal worldwide. There are risk factors that lead to preeclampsia in the pregnant woman. The purpose of this study was to determine the risk factors which most influence the incidence of preeclampsia. This was an observational analytic study with case-control study design. The populations were all pregnant and postpartum mothers who were treated in RSUD dr. Soeselo Slawi from January to June 2018. Total of samples were 222 which consist of 111 cases and 111 control sample. The sampling method of the case used simple random sampling technique. Data were obtained from medical records. The analyses which used in this study were chi-square test and multiple logistic regression. The results showed there were a significant difference between the previous preeclampsia (p-value = 0,047), hypertension (p-value = 0,000), and diabetes mellitus (p-value = 0,057) in the case group and the control group. Multiple logistic regression analysis showed that hypertension is the most dominant risk factor that causes preeclampsia. Previous preeclampsia, hypertension, and diabetes mellitus are the risk factors that most influence the incidence of preeclampsia.